John C. White, Digest of the Laws and Ordinances of the Parish of East Feliciana, Adopted by the Police Jury of the Parish 68 (1848) - (:unkn) unknown (General Publisher, 1848)
Prohibited any “slave” from carrying a gun off the plantation without the permission.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES